Changes in daily routines and health-related quality of life among Spanish older adults after the COVID-19 pandemic: analysis from a gender perspective - Cameselle-Lago, Candela; Rico-Blázquez, Milagros; Sánchez-Ruano, Raquel; Ayala, Alba; Pascual-García, Marcos; Solé-Agustí, María; Gimeno-Pi, Iraida; Echevarria-Echevarria, Aitziber; González-Chordá, Víctor M.; Esteban-Sepúlveda, Silvia; Pedraz-Marcos, Azucena; Company-Sancho, María Consuelo; et al. (Frontiers in Public Health, 2025)
AimsTo examine the association between perceived changes in daily routines due to the COVID-19 pandemic and health-related quality of life (HRQoL) among community-dwelling adults aged 75 and older in Spain, through a gender-stratified analysis.DesignCross-sectional, community-based, multicentre study using baseline data from the CUIDAMOS+75 cohort.MethodsA total of 1,072 older adults over 75 from 11 Spanish regions were interviewed between June 2022 and June 2023. Data on SARS-CoV-2 exposure, sociodemographic and clinical characteristics and perceived changes in daily routines (basic-needs, healthcare and social routines) were collected. HRQoL was measured using the EQ-5D-5L utility index. Gender-stratified linear regression models were used to examine associations between changes in routines and HRQoL.ResultsOver half of the participants (52%) reported considerable changes in their daily routines due to the pandemic, especially in social routines (48%). Women reported more frequent changes across all routine types. Although women had lower overall HRQoL scores, changes in routines were more strongly associated with poorer HRQoL among men, particularly when healthcare routines were affected. Among women, significant associations were observed for disruptions in combined basic and social routines as well as when all three routine types were simultaneously affected. Notably, COVID-19 infection status was not associated with HRQoL after adjustment.ConclusionThe COVID-19 pandemic led to substantial and persistent changes in daily routines among older adults in Spain, with gender-specific patterns in their association with HRQoL. These findings highlight the importance of incorporating a gender perspective in public health responses to health crises, particularly in strategies aimed at preserving daily routines to support autonomy and wellbeing in older populations.